2018
DOI: 10.1016/j.jacc.2018.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin or Heparin in Patients Undergoing Invasive Management of Acute Coronary Syndromes

Abstract: In patients with ACS, the rates of MACEs and NACEs were not significantly lower with bivalirudin than with UFH, irrespective of planned GPI use. However, bivalirudin significantly reduced bleeding complications, mainly those not related to access site, irrespective of planned use of GPIs. (Minimizing Adverse Haemorrhagic Events by Transradial Access Site and Systemic Implementation of AngioX [MATRIX]; NCT01433627).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Although the role of anticoagulants in the secondary prevention of recurrent ischemic events after acute coronary syndrome (ACS) and during percutaneous coronary intervention (PCI) in stable coronary artery disease (CAD) is well established [5][6][7][8], the possible increase in ischemic coronary events with anticoagulants in different clinical settings is a matter of concern [2,6,9,10]. In this context, enoxaparin, a low molecular weight heparin (LMWH) with predominant anti-Xa mechanism, was shown to be safe in other studies, without pro-aggregatory effects [4,5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of anticoagulants in the secondary prevention of recurrent ischemic events after acute coronary syndrome (ACS) and during percutaneous coronary intervention (PCI) in stable coronary artery disease (CAD) is well established [5][6][7][8], the possible increase in ischemic coronary events with anticoagulants in different clinical settings is a matter of concern [2,6,9,10]. In this context, enoxaparin, a low molecular weight heparin (LMWH) with predominant anti-Xa mechanism, was shown to be safe in other studies, without pro-aggregatory effects [4,5,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…10 Similar findings were observed in the MATRIX antithrombin study, regardless of the concurrent therapy with GPIs or access site. 7 Collectively, these trials have consistently shown reduced bleeding events with bivalirudin, despite the differences in their design including variable use of P2Y 12 inhibitors and GPIs, and In conclusion, in patients undergoing TRI, bivalirudin was associated with reduced short-term NACE compared with heparin. There were no significant differences between groups with regard to other short-and long-term ischemic and bleeding events.…”
Section: Discussionmentioning
confidence: 94%
“…4 However, the added ischemic benefit from GPIs was offset by increased bleeding-a risk that has been linked with mortality. [5][6][7] In contrast to heparin, bivalirudin is a short-lived direct thrombin inhibitor with an intrinsic antiplatelet activity and more stable pharmacokinetic and pharmacodynamic properties which has been associated with reduced bleeding, primarily in trials utilizing femoral artery access. 8 However, the efficacy and safety outcomes of bivalirudin administration in patients undergoing transradial artery coronary interventions (TRI) are conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…1 Both unfractionated heparin (UFH) and bivalirudin are used as antithrombin strategies during PPCI. [2][3][4][5][6][7] Remaining thrombus within the stented infarct-related artery has been consistently observed with optical coherence tomography (OCT) at the end of PPCI. 8,9 This residual thrombosis of stent struts may promote further thrombus growth and represent a risk factor for acute stent thrombosis.…”
Section: Introductionmentioning
confidence: 87%
“…Patients presenting with acute ST‐elevation myocardial infarction (STEMI) receive primary percutaneous coronary intervention (PPCI) as the treatment of choice 1 . Both unfractionated heparin (UFH) and bivalirudin are used as antithrombin strategies during PPCI 2–7 …”
Section: Introductionmentioning
confidence: 99%